1997
DOI: 10.1128/jb.179.20.6512-6517.1997
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct models account for short and long deletions within sequence repeats in Escherichia coli

Abstract: In Escherichia coli, (GpC) n sequences cloned into plasmid DNA molecules are deletion-prone with the occurrence of both short (<2 bp) and long (>2 bp) deletion events. These repetitive tracts can be stabilized by interrupting the strict monotony of the repetition with a variant dinucleotide sequence. The stabilization of short deletion events that is mediated by the variant sequence is completely lost in E. coli mismatch repairdeficient strains. In contrast, this repair pathway has no influence on the frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
7
2
Order By: Relevance
“…Dinucleotide repeat tracts are destabilized by inactivation of any of the nonredundant major components of the E. coli MMR system (24,31). Previously, using a chromosomally located mod-AT20R-lacZ reporter gene, we showed that inactivation of H. influenzae mutS destabilized a tract of 20 5Ј AT dinucleotide repeats (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinucleotide repeat tracts are destabilized by inactivation of any of the nonredundant major components of the E. coli MMR system (24,31). Previously, using a chromosomally located mod-AT20R-lacZ reporter gene, we showed that inactivation of H. influenzae mutS destabilized a tract of 20 5Ј AT dinucleotide repeats (5).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of the spectra of spontaneous mutations for wild-type strains and MMR mutants reveal that MMR is active on all types of base substitutions and frameshifts, with the latter occurring most frequently in short tracts of the same base pair (23,30). Long DNA repeat tracts, termed microsatellites, with unit sizes of 1 or 2 nucleotides are highly unstable in E. coli MMR mutants (24,31,33), while the mutation rates of tetranucleotide repeat tracts are unaltered (10).…”
mentioning
confidence: 99%
“…It is also reminiscent of the behavior of microsatellites (also called short sequence repeats: SSR, see [45] for review), which are stabilized by internal variations [46] and by reduction of the number of repeats [47]. Unfortunately, we show here that such simple prediction criteria may miss a very large proportion of polymorphic tandem repeats, and provide highly variable results in different species.…”
Section: Discussionmentioning
confidence: 94%
“…For example, mis-pairs or small loop structures in repetitive DNA will be excised by mismatch repair or nucleotide excision repair proteins leading to DNA gaps. 21,[39][40][41][42][43][44][45][46][47][48] If these gaps are sufficiently long, secondary structures such as hairpins may be formed in the single-stranded repeat regions. Most models for deletions propose that during polymerization to fill in the gaps, the DNA polymerase will bypass the template hairpin structure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Several cellular factors have been shown to influence repeat stability including transcription, [20][21][22][23] DNA polymerase proofreading, [24][25][26] and DNA methylation. [27][28][29][30] Nevertheless, the three main DNA metabolic pathways (DNA replication, [31][32][33][34][35] recombination, [36][37][38] and repair 21,[39][40][41][42][43][44][45][46][47][48] have the strongest impact on genetic instabilities.…”
Section: Introductionmentioning
confidence: 99%